THYROID GLAND, ANOTHER VICTIM OF COVID-19? ABOUT A CASE - Paz-Ibarra, Jose (2020)
Coronavirus disease compromises all biological organs and systems, either by direct commitment to specific tissues or by indirect effects. The endocrine system is no exception, and parenchyma and thyroid function have been reported to be impaired. In 2003 a histopathological study on the effects of SARS-CoV infection on the thyroid showed extensive damage to parafollicular cells and destruction and exfoliation of epithelial cells in the thyroid follicle, an interesting finding was the absence of an inflammatory infiltrate. which supported the hypothesis of extensive apoptosis responsible for the findings. In China, minimally invasive autopsies of different organs of patients who died of SARS-CoV-2 did not report abnormalities in thyroid follicular morphology, but noted lymphocytic infiltration in the interstitium; none of the tissue immunohistochemistry and PCR analyzes detected SARS-CoV-2 in the thyroid. The first case of thyroid alteration compatible with subacute thyroiditis in a patient with COVID-19 in Peru is presented.